Existence and uniqueness of solution of the Cauchy problem for singular systems of integro-differential equations - Shmarda, Z. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Sufficient conditions are established for the existence of a unique solution of the Cauchy problem for singular systems of integro-differential equations.